Predicting the Mental Health of Multiple Sclerosis (MS) Patients based on Relationship Quality, Early Maladaptive Schemas, and Fear of Disease Progression - Soraya Khanlari Aziz; Mahnaz Shahgholian; Mohammad Hossein Abdollahi (Iranian Evolutionary Educational Psychology Journal, 2023)
The aim of this study was to forecast the mental well-being of individuals with multiple sclerosis (MS) by considering the quality of their family relationships, early maladaptive schemas, and their fear of disease progression. The research employed a descriptive-correlational design. The research subjects encompassed MS patients in the Kermanshah and Alborz provinces (Iran) during the year 2020. The sampling technique used was convenience sampling, leading to the selection of a total of 83 patients who actively participated in the research by completing questionnaires. The research tools utilized included the Mental Health Questionnaire (SCL-25), a shortened version of the Young Schema Questionnaire (YSQ – SF), the Quality of Relationships Questionnaire (QRI), and the brief form of the Fear of Disease Progression Questionnaire (FOP-Q-SF). Data analysis was carried out using SPSS version 24. The findings of the data analysis revealed a significant and positive association between all aspects of early maladaptive schemas and the mental well-being of MS patients. Conversely, none of the elements of the quality of relationships displayed a substantial connection with the mental health of MS patients. Furthermore, there was a significant and positive correlation between the fear of disease progression and the mental well-being of MS patients. Regression analysis results demonstrated that the variables of early maladaptive schemas and fear of disease progression collectively accounted for 52% and 35% variance of the mental health of MS patients, respectively. Given the unique attributes of MS, it is vital to focus on the mental well-being of these individuals. Exploring and examining other psychological variables can contribute to a deeper comprehension of the mental health of this particular group.